Die lewe en werk van Rudolf Bultmann (1884–1976): ŉ Leksikografiese bydrae tot Reformasie 500 - Wyk, Gabriël M. J.van (HTS teologiese studies, 2017)
Rudolf Bultmann was one of the leading thinkers within an influential theological direction that arose in Europe after the First World War, known as dialectical theology. Comprehensive introductions to the life and work of Bultmann in the South African theological journals, written in Afrikaans, either does not exist, or are difficult to trace for the Afrikaans readership. This article on Bultmann aims to fill the gap by offering a lexicographical contribution on the life and work of Bultmann. The focus of this article is on Bultmann as a Lutheran thinker. The theme of the New Testament and systematic theology is essentially the same, namely to explain the concept of Christian self-understanding as an eschatological event in which faith is expressed for the sake of faith in God and only in God. Bultmann explained the same theological concepts with his theology as those that were explained by the church reformers of the 16th century, but under radically new circumstances. The so-called modern and postmodern people of our time not only broke ties with the past, but in the process they also lost their ability for using historical-critical patterns of thought that tries to bridge historical distances, and therefore sacrificed all efforts to think systematically on the altar of relativism. We can learn from Bultmann what systematic reformed theology really is.